Twin tunnel excavation in coarse grained soils: Observations and numerical back-predictions under free field conditions and in presence of a surface structure. (June 2015) - Fargnoli, V.; Boldini, D.; Amorosi, A.
Graphical abstract: Highlights: This paper is focused on the effect of twin-tunnelling on ground and structure settlements. Reference is made to the recent EPB excavation of the metro-line 5 in Milan (Italy). Ground and structure settlement measurements are collected and interpreted. The problem is also analysed by an integrated, geotechnical and structural, 3D FE approach. The proposed FE approach is validated against in situ monitoring data. Abstract: In this paper the effects induced by twin-tunnelling on ground and structure settlements is analysed and discussed. The study refers to the case of the Milan metro-line 5, recently excavated in coarse-grained materials using earth pressure balance machines. Firstly, settlement measurements under free-field conditions are back-interpreted using the classical Gaussian empirical predictions, providing a detailed description of the modification of the subsidence profile due to the second excavation with respect to the single tunnel configuration. The in situ measurement analysis is subsequently extended to explore the evolution of the structural response of a nine-storey reinforced concrete surface building, undercrossed by the metro-line, as observed during the tunnelling activities. In the second part, the paper illustrates a three-dimensional finite element back-analysis of the above case history. The soil mechanical behaviour is described by an advanced constitutive model (named Hardening Soil model with small strain stiffness ), the twin-tunnelling is properly schematised taking into account the main aspects of the excavation sequence and the building is modelled in a realistic fashion in terms of geometry, stiffness and weight properties. The computed results, in good agreement with the settlement monitoring data, are capable to capture the interaction phenomena occurring between the twin tunnels during the construction works and to describe the evolution of the deformative mechanisms affecting the building façades.